Proadrenomedullin Predicts Severe Disease in Children With Suspected Community-acquired Pneumonia - Florin, Todd A (Clin Infect Dis, 2020)
BACKGROUND: Proadrenomedullin (proADM), a vasodilatory peptide with antimicrobial and anti-inflammatory properties, predicts severe outcomes in adults with community-acquired pneumonia (CAP) to a greater degree than C-reactive protein and procalcitonin. We evaluated the ability of proADM to predict disease severity across a range of clinical outcomes in children with suspected CAP. METHODS: We performed a prospective cohort study of children 3 months to 18 years with CAP in the emergency department. Disease severity was defined as mild (discharged home), mild–moderate (hospitalized but not moderate–severe or severe), moderate–severe (eg, hospitalized with supplemental oxygen, broadening of antibiotics, complicated pneumonia), and severe (eg, vasoactive infusions, chest drainage, severe sepsis). Outcomes were examined using proportional odds logistic regression within the cohort with suspected CAP and in a subset with radiographic CAP. RESULTS: Among 369 children, median proADM increased with disease severity (mild: median [IQR], 0.53 [0.43–0.73]; mild–moderate: 0.56 [0.45–0.71]; moderate–severe: 0.61 [0.47–0.77]; severe: 0.70 [0.55–1.04] nmol/L) (P = .002). ProADM was significantly associated with increased odds of developing severe outcomes (suspected CAP: OR, 1.68; 95% CI, 1.2–2.36; radiographic CAP: OR, 2.11; 95% CI, 1.36–3.38) adjusted for age, fever duration, antibiotic use, and pathogen. ProADM had an AUC of 0.64 (95% CI, .56–.72) in those with suspected CAP and an AUC of 0.77 (95% CI, .68–.87) in radiographic CAP. CONCLUSIONS: ProADM was associated with severe disease and discriminated moderately well children who developed severe disease from those who did not, particularly in radiographic CAP.